Electric field effects during nucleate boiling from an artificial nucleation site - ROBINSON, ANTHONY (My University, 2011)
An experimental study of saturated pool boiling from a single artificial nucleation site on a polished copper surface has been performed. Isolated bubbles grow and depart from the artificial cavity and the bubble dynamics are recorded with a high speed camera. Experimental results are obtained for bubble growth, departure and vertical rise both with and without the application of an electric field between an upper electrode and the boiling surface. As detailed in a previous paper from the same research group the high spatial and temporal resolution of the video sequences facilitated the development of a baseline experimental bubble growth law which predicts the bubble volumetric growth characteristics for a range of surface superheats at atmospheric pressure. The presence of an electric field has been found to positively augment the convective heat transfer over that of buoyant natural convection. Further to this, for high electric field strengths, the bubble shape, volumetric growth characteristics and bubble rise are different from that of the baseline cases. These results provide compelling evidence that electric fields can be implemented to alter the bubble dynamics and subsequent heat transfer rates during boiling of dielectric liquids
PUBLISHED
Keywords: Mechanical and Manufacturing Engineering; bubble dynamics